An accessory renal aneurysm in a patient with absent renal artery: a case report - Wan, Jianghong; Chen, Chu Wen; Chen, Guoxin; Huang, Bin (Frontiers in Cardiovascular Medicine, 2024)
Informed consent: Written informed consent was obtained from the individual for the publication of any potentially identifiable images or data included in this article.Author contributions: Jianghong Wan and Chuwen Chen wrote the manuscript, and they were cofirst authors. Guoxin Chen was responsible for tracking patient follow-up results. Bin Huang was the chief operating surgeon and was responsible for the revision of the manuscript for important intellectual content. All authors issued final approval for the version to be submitted.